ETR 300 : Busana Wahidah Muslimah Fashion Centre / Azlyn Ahmad Zawawi ... [et al.] - Zawawi, Azlyn Ahmad; Abd Rahim, Wan Fatonatunnor; Nordin, Normawati; Jaafar, Noor Khairulnisa'; Majid, Nor Asmah (2001)
Busana Wahidah Muslimah Fashion Center is a final idea of five partners whom have been interested with this nature of business. Focusing on Muslimah's fashion and attire, Busana Wahidah aims to serve all Muslim women with the latest and variety of fashion in the market by not neglecting their status and title as Muslimah. The motto of Busana Wahidah is' Our attire is the mirror to our personality'. The products of Busana Wahidah are not only baju kurungs but it also covers all types of scarves, dresses and blouses. The textile used in this business grade from the cheapest to the most expensive type of textile. The business also aims to fulfill the market needs which by our observations, lack of Muslimah's fashion. In this modem era, Islamic fashions are not only limited to baju kurungs and chasuble only but it has been expanding wider and more creative. The establishment of Busana Wahidah is hoped to fill the needs and requirements of all Muslimah that are fashionable especially working women and youths. Busana Wahidah's mission is also to provide all Muslimah with the kind of fashion they need and at the same time following the guidelines and are subjected to Islam and it's Syariat.